Pedagogical cases in physical education and youth sport - Armour, Kathleen (London Routledge, 2014)
"Pedagogical Cases in Physical Education and Youth Sport is a completely new kind of resource for students and practitioners working in physical education or youth sport. The book consists of 20 richly described cases of individual young learners, each written by a team of authors with diverse expertise from across the sport, exercise and movement sciences. These cases bring together knowledge from single sub-disciplines into new interdisciplinary knowledge to inform best practice in physical education, teaching and coaching in youth sport settings. At the heart of each case is an individual young person of a specified age and gender, with a range of physical, social and psychological characteristics. Drawing on current research, theory and empirical data from their own specialist discipline, each chapter author identifies the key factors they feel should be taken into account when attempting to teach or coach the young person described. These strands are then drawn together at the end of each chapter and linked to current research from the sport pedagogy literature, to highlight the implications for planning and evaluating teaching or coaching sessions. No other book offers such a rich, vivid and thought-provoking set of pedagogical tools for understanding and working with children and young people in sport. This is an essential resource for any student on a physical education, coaching, kinesiology or sport science course, and for any teacher, coach or instructor working in physical education or youth sport"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Physical education and training -- Case studies; Physical education for youth -- Case studies; Sports for children -- Case studies; Coaching (Athletics) -- Case studies